CDC42 and EZH2 are overexpressed in colorectal cancer: Are they minimal invasive diagnostic markers? Minimal invasive diagnostic markers for CRC - Denkçeken, Tuba; Onur , Elif; Şahin, Mehmet; Milli, Rabia (Journal of Surgery and Medicine, 2025)
Background/Aim: Bioinformatics methods have been used to show that cell division cycle 42 (CDC42) and enhancer of zeste homolog 2 (EZH2) have potential oncogenic effects in colorectal cancer (CRC). In this study, we performed experimental validation of these genes. Methods: We considered the possible role of CDC42 and EZH2 genes in SW480 and SW620 cells. Furthermore, blood samples were gathered from CRC patients and healthy controls to compare CDC42 and EZH2 levels, and relative mRNA and protein levels were measured. Results: CDC42 and EZH2 expression levels were significantly increased in the SW480 and SW620 cell lines when compared with normal CRL-1790. In addition, when we examined CDC42 and EZH2 expression levels in blood samples of 20 CRC patients and 20 healthy controls by RT-qPCR, the levels of CDC42 and EZH2 were significantly upregulated in patients with CRC compared with healthy control subjects. Similar results were obtained in terms of the protein expression levels of CDC42 and EZH2. Conclusion: These data reveal that CDC42 and EZH2 are significantly overexpressed in CRC. Considering that high gene and protein expression levels of CDC42 and EZH2 were found in the serum of patients suffering from CRC, these two genes may be developed as minimally invasive diagnostic markers for CRC detection.